Sulfur corrosion mechanism in power transformers and its detection techniques: a review - Ahmad Khiar, Mohd Shahril; Ab Ghani, Sharin; Abu Bakar, Norazhar; Sutan Chairul, Imran; Talib, Mohd Aizam (Institute of Electrical and Electronics Engineers Inc., 2022)
Monitoring the progression of sulfur corrosion in insulating oils, particularly mineral oils, gives valuable information on the general health of the power transformers, thus preventing the possibility of catastrophic failures. The sulfur corrosion mechanism in insulating oils remains unclear although it is believed that this phenomenon is initiated by the presence of corrosive by-products of dibenzyl disulfide (DBDS) (i.e., mercaptans and elemental sulfur). A number of models have been developed that explain the chemical reactions, formation, and deposition of copper sulfide in power transformers. Irrespective of the sulfur corrosion mechanism, monitoring the progression of sulfur corrosion in power transformers is crucial before effective countermeasures can be implemented. The capability and limitations of standard and non-standard corrosion test methods based on the quality of the insulating oils and paper insulations are extensively reviewed in this article. This sets out the ultimate goal of searching for a reliable and quantifiable online condition monitoring tool to track the progression of sulfur corrosion in transformer insulating oils in real-time and facilitate timely remedial intervention.